Situaciones de comparación social y afectos negativos en universitarios: un reporte de investigación - León Donayre, Ramón (1998)
A total of 326 students (163 men and 163 women, with ages between 16 and 22 years) of a private university in Lima rated 23 daily situations involving social comparison as causes of four negative affect: jealousy/envy, anger, sadness, and embarrassment, in a 4 points scale (()=nothing, 4=very strong). The situation which caused the highest intensity of the four effects was "someone else gets credit for what you have done", followed by "you do the same work as someone else and get paid less than him o her". The intensity of the negative affects caused by these situations is an evidence of the importance that students give to equity as a social value.